THE PORTRAIT OF AN ACTIVE WOMAN IN UZBEKISTAN CLASSICAL LITERATURE - Rahmonova Shahlo Rashidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the oral poetry of the Uzbek people, we can find the image of an active woman in dozens of epics of the Uzbek people, such as "Alpomish", "Gorogli", "Takhir va Zuhra", "Kuntugmish". In these sagas, the image of women occupies a large place. In classic literature, we can see the richness of the issue of socially active women with the works of great word artists such as Khorezmi, Sayqali, Sayyad, Lutfii and Navoi, Babir and Muhammad Salih, Turdi and Mashrab, Nadira and Uvaisi, Munis and Ogahi. In particular, we can see the achievements of Navoi’s heroes in state management, active in social life, learning, and profession, and through this, they are no less than others. In Navoi’s works and epics, a woman’s activity, enlightenment, hard work for the well-being of people, talent and talent are embodied in artistic images. In Uzbek folk oral poetry and classical literature, it is analyzed that social female figures are in tune with today’s times in matters such as the education of the people’s children and the acquisition of professions.